2019
DOI: 10.5217/ir.2018.00022
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is associated with disease activity in patients with Crohn’s disease

Abstract: Background/AimsPrevious data suggest that vitamin D has a significant role in inflammatory bowel disease (IBD). We investigated the incidence of vitamin D deficiency in Korean patients with IBD and the correlation between serum vitamin D level and disease activity.MethodsWe retrospectively analyzed the medical records of patients with IBD whose serum vitamin D levels were checked. Deficiency of 25-hydroxyvitamin D was defined as <20 ng/mL. Disease activity was evaluated using the partial Mayo score for ulcerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
3
21
0
1
Order By: Relevance
“…Some studies on CD reported that low levels of vitamin D is associated with Crohn's disease activity, 18,19 while others showed no such association. 7,20 Exploring this relationship is difficult and complex because many variables are involved in evaluating disease activity. In contrast to our findings, Jorgensen et al 21 found an inverse association between serum 25[OH]D and disease activity in CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on CD reported that low levels of vitamin D is associated with Crohn's disease activity, 18,19 while others showed no such association. 7,20 Exploring this relationship is difficult and complex because many variables are involved in evaluating disease activity. In contrast to our findings, Jorgensen et al 21 found an inverse association between serum 25[OH]D and disease activity in CD patients.…”
Section: Discussionmentioning
confidence: 99%
“…As well as regulating bone, calcium, and phosphorus metabolism, Vitamin D has a key role in intestinal defense mechanisms, regulating the adaptive and innate immune systems and suppressing microbial invasion of the epithelium [105,106]. Vitamin D deficiency has been detected in 16% to 95% of IBD sufferers, mainly in CD patients [107]. This may be due to several factors, such as intestinal malabsorption, low exposure to sunlight, lack of physical activity, or insufficient dietary intake.…”
Section: Micronutrientsmentioning
confidence: 99%
“…Thus, VitD deficiency may play a role in the development of IBD and its severity. Other studies, however, have taken the opposite view of the relationship [15] between VitD and IBD and have left the controversy unresolved for patients with CD [16] and UC [17, 18]. Therefore, to explore this controversy we performed a pooled meta-analysis to investigate and determine the status of VitD in the serum of healthy and non-healthy controls and to study the association between serum 25(OH)D and 1,25(OH) 2 D 3 concentrations and an IBD diagnosis (both UC and CD).…”
Section: Introductionmentioning
confidence: 99%